The Effects of Infusing Thrombin and Its Acetylated Derivative - Bennett, J. M; Yu, Dinah; Suyemoto, J; Pechet, L (Thrombosis and Haemostasis, 1968)
In conjunction with experiments designed to test the effects of infusing acetylated thrombin (Thrombin E) and Clotting thrombin (Thrombin C) into dogs, the occurrence of hemolysis was noted. Serial observations on its magnitude, its relationship to thrombin-induced defibrination, and the formation of thrombi were made. The findings suggest a unique role for thrombin in inducing “in vivo” intravascular hemolysis in short term experiments, possibly via an indirect action on red blood cells.